Firearm Involvement in Delinquent Youth and Collateral Consequences in Young Adulthood: A Prospective Longitudinal Study, Chicago, Illinois, 1995-1998 - Teplin, Linda A. ([Verlag nicht ermittelbar], 2020)
This study contains data from the Northwestern Juvenile Project (NJP) series, a prospective longitudinal study of the mental health needs and outcomes of youth in detention. This study examined the following goals: (1) firearm involvement (access, ownership, and use) during adolescence and young adulthood; (2) perpetration of firearm violence over time; and (3) patterns of firearm victimization (injury and mortality) over time. This study addressed the association between early involvement with firearms and firearm-firearm perpetration and victimization in adulthood. The original sample included 1,829 randomly selected youth, 1,172 males and 657 females, then 10 to 18 years old, enrolled in the study as they entered the Cook County Juvenile Temporary Detention Center from 1995 to 1998. Among the sample were 1,005 African Americans, 524 Hispanics, and 296 non-Hispanic white respondents. Participants were tracked from the time they left detention. Re-interviews were conducted regardless of where respondents were living when their follow-up interview was due: in the community, correctional settings, or by telephone if they lived farther than two hours from Chicago.